The Fluctuation of Intraocular Pressure Measured by a Contact Lens Sensor in Normal-Tension Glaucoma Patients and Nonglaucoma Subjects. Issue 3 (March 2017) - Tojo, Naoki; Abe, Shinya; Ishida, Masaaki; Yagou, Takaaki; Hayashi, Atsushi
Abstract : Purpose: We compared the fluctuation of intraocular pressure (IOP) in normal-tension glaucoma (NTG) patients and individuals with nonglaucoma eyes. We obtained continuous IOP values using a SENSIMED Triggerfish contact lens sensor. Materials and Methods: The eyes of 12 nonglaucoma subjects and 14 NTG patients were examined. In all 26 subjects, the IOP fluctuation was measured continuously for 24 hours with a contact lens sensor. We evaluated the range of IOP fluctuations over the 24-hour period separately for diurnal IOP and nocturnal IOP and identified each subject's maximum value. The range of IOP fluctuation were analyzed, cutoff level of IOP fluctuation was calculated using receiver operating characteristic curve analyses. Results: The mean IOP in the NTG eyes was 11.5±2.4 mm Hg and that in the nonglaucoma eyes was 12.7±2.0 mm Hg, a nonsignificantly difference ( P =0.175). The 24-hour range of IOP fluctuations in the NTG group was significantly larger than that of the nonglaucoma group ( P =0.007). The percentage of NTG patients who had the peak time of IOP fluctuation during nocturnal sleep was 57.1%, whereas the corresponding rate for the nonglaucoma eyes was 91.7%. The cutoff level of IOP fluctuation for glaucoma was 442 mVeq (sensitivity=1.00; specificity=0.571). Conclusions: The range of IOP fluctuation was larger in the eyes with NTG than in the nonglaucoma eyes. This larger fluctuation might be one of the reasons underlying the aggravation of the visual field by NTG. Measurements of 24-hour continuous IOP might be one of the useful methods to distinguish NTG from nonglaucoma eyes.